The effects of internal displacement on the host border regions (case study of the Lviv Region of Ukraine) - Lozynskyy, Roman. Autor; Pantyley, Viktoriya. Autor; Zubyk, Andriy. Autor; Smaliychuk, Hanna. Autor (IGiPZ PAN, 2023)
The study objective is to analyse the effect of the flow of internally displaced persons (IDPs) on the development of the Lviv Oblast – the largest region of Ukraine bordering on the EU. The article was based on available statistical data (most statistical data in Ukraine under martial law is not made public), data from sociological research of international organisations, and other official public sources of information. The study results suggest that the Lviv Oblast has become the main Ukrainian transit region on the route of refugees from Ukraine across the border, as well as one of the main oblasts accepting IDPs. At least 5 million people have passed the oblast in transit, and the number of IDPs reached its maximum in the period May-June 2022. Most of the people arrived in the city of Lviv, other large cities, as well as recreation and tourist centres. IDPs have had a positive effect on the sectors of housing construction and tourism in the oblast, and contributed to an increase in the budget income of separate territorial hromadas. Approximately 230 enterprises have also been relocated to the oblast. Most IDPs are planning or expect to return to their former place of residence, although with each month of war duration, the share of people integrating with local communities and planning to permanently remain in the territory of the Lviv Oblast increases. In spatial terms, the flow of IDPs considerably exceeded the level of urbanisation of the oblast, and accelerated the development of the Lviv urban agglomeration. In the future perspective it may contribute to an increase in territorial disproportions between large cities in the oblast, with better developed hromadas around Lviv, mountain and pre-montane towns on the one hand, and depressive hromadas in the east and south-east of the oblast on the other.
29 cm
Każdy numer posiada własny tytuł.
Keywords: kryzys humanitarny; osoby przesiedlone za granicę; Lwów; obwód lwowski; rosyjska agresja militarna; Ukraina